(untitled) (American Journal of Islam and Society, 1986)
I. The Need Just as philosophical and religious writings are a verbal expression of the ideology of a people, just as social and economic institutions are determined by that basic ideology, so also music and the sound arts are "aanslations" of the deepest convictions of a people. They fit into the cultural whole as pieces of a giant mosaic, each tessera reflecting the world view of that people and corresponding to the other expressions of that spirit. Fulfilling this role in the culture, the arts of sound become an important, even crucial, bulwark of a people’s heritage. In English, such aesthetic "translations" of the ideology into pitches and durations are known as "music"; and the term has generally encompassed all forms of sound art, regardless of their intrinsic characteristics or the circumstances of their performance. In Islamic culture, however, there is no term or expression which includes all types of sound art. The term musiqa, which is sometimes loosely equated with the English term "music," is certainly inadequate. That Arabic term derived from the Greek has been applied primarily to those forms which, because of context of performance or aesthetic characteristics, were culturally and religiously regarded with some degree of suspicion, or in certain cases, even condemned. The term miidqii has never included those genres of sound art which were wholeheartedly approved and fostered by the culture, e.g., Qur’anic chant, the adhan, the pilgrimage chants, madih chanted poetry (shi’r). Elsewhere I have therehre advocated the use of a new expression, Handasah al sawt (al Faruqi 1982:30ff). This designation would cover all the forms of sound art, and thus more truly equate with the term "music" and its cognates in other European languages. It is with that expression and an appreciation of the wide meaning which it implies that this presentation continues. Handasah al sawt is a cultural phenomemon which can play an important ...